Assessment Of Designed And Measured Mechanistic Parameters Of Concrete Pavement Foundation - Yang Zhang; Pavana Vennapusa; David Joshua White (The Baltic Journal of Road and Bridge Engineering, 2019)
There are plenty of in situ tests available to examine pavement foundation performance regarding stiffness and support conditions. This study evaluates several in situ tests of the stiffness and support conditions of concrete pavement foundation layers. The principal objective of this study was to evaluate the outputs from Dynamic Cone Penetrometer tests and Falling Weight Deflectometer tests. The California Bearing Ratio from Dynamic Cone Penetrometer tests and the deflection data from Falling Weight Deflectometer tests were correlated to the design parameter – modulus of subgrade reaction k through correlations employed in pavement design manuals. Three methods for obtaining the k values were conducted, with the intent to evaluate which method provides the results most similar to the target value and whether the studied correlations are reliable. The back-calculated k values from Falling Weight Deflectometer deflections and the weak layer California Bearing Ratio correlated k values based on the Portland Cement Association method were close to the target value, while the California Bearing Ratio empirically correlated k based on the American Association of State Highway and Transportation Officials method presented values significantly higher than the target value. Those previously reported correlations were likely to overestimate the k values based on subgrade California Bearing Ratio values.